2017
DOI: 10.1021/acs.molpharmaceut.7b00740
|View full text |Cite
|
Sign up to set email alerts
|

Absorptive Dissolution Testing of Supersaturating Systems: Impact of Absorptive Sink Conditions on Solution Phase Behavior and Mass Transport

Abstract: One of the most commonly used formulation development tools is dissolution testing. However, for solubility enhancing formulations, a simple closed compartment conventional dissolution apparatus operating under sink conditions often fails to predict oral bioavailability and differentiate between formulations. Hence, increasing attention is being paid to combined dissolution-absorption testing. The currently available mass transport apparatuses, however, have certain limitations, the most important being the sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 42 publications
1
42
1
Order By: Relevance
“…These results contradict previously published results by, for example Bevernage et al ., Hate et al . and Berben et al ., who saw that the inclusion of an absorptive compartment stabilized a supersaturated system and decreased the amount of precipitation . However, as both the model drugs (loveride and nevirapine) and experimental model setup (shaken Caco‐2 Transwells, use of hollow fibres and the AMI system) in the study by Bevernage et al ., Hate et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results contradict previously published results by, for example Bevernage et al ., Hate et al . and Berben et al ., who saw that the inclusion of an absorptive compartment stabilized a supersaturated system and decreased the amount of precipitation . However, as both the model drugs (loveride and nevirapine) and experimental model setup (shaken Caco‐2 Transwells, use of hollow fibres and the AMI system) in the study by Bevernage et al ., Hate et al .…”
Section: Resultsmentioning
confidence: 99%
“…In their setup, drug absorption was mimicked using a hollow fibre membrane module with a surface area of 115 cm 2 , and a continuous flow of donor (50mL) and acceptor media on either side of a membrane, which allowed a 30 times higher mass transfer of the weak base nevirapine, as compared to using a side‐by‐side diffusion cell . Using the high surface area, flow‐through absorptive dissolution model, Hate et al insured a A/V ratio of 2.3 cm −1 and showed that the presence of an absorptive compartment during dissolution studies can alter the crystallization kinetics of nevirapine formulations. At low levels of supersaturation, drug absorption inhibited drug precipitation; however, at high levels of supersaturations, nevirapine precipitated rapidly independently of absorption .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 A number of techniques have been employed to achieve sink or near sink conditions viz. (1) increasing the dissolution media volume (typically up to 900-1000 mL in USP I and II apparatus), (2) addition of solubility enhancers such as surfactants, 10 (3) continuous media change flow through cell (USP IV) apparatus, [11][12][13] (4) integrating sink dialysis bag, or (5) use of an additional (organic) phase into which drug can partition. [14][15][16][17][18] The 2-phase in vitro system contains an aqueous medium within which the drug product undergoes dissolution and an additional (immiscible) organic layer to simulate an absorptive sink.…”
Section: Introductionmentioning
confidence: 99%
“…The Simcyp In Vitro data Analysis (SIVA) toolkit supports the analysis of complex in vitro data and allows seamless in vitroin vivo extrapolation (IVIV_E), which is a key element in successful prediction of in vivo behavior with physiologically based pharmacokinetic (PBPK) models. 11 The underlying principle of biopharmaceutical IVIV_E and its application in PBPK prediction sciences have already been explained in detail elsewhere. [20][21][22] The SIVA toolkit thus assists with the analysis of complex data generated from biopharmaceutic experiments for solubilitydsimple buffers and simulated intestinal fluidsdand dis-solutiondUSP II, USP IV, transfer models, media change experiments, 2-phase, mDiss etc.…”
Section: Introductionmentioning
confidence: 99%